Abdominal manifestation of multisystemic inflammatory syndrome in children - Iván José Ardila Gómez; Pilar Pérez López; Darling Carvajal Duque; Doris Martha Salgado García; Andres Felipe Romero; Martha Rocío Vega Vega; Jorge Andres Ramos Castañeda (Elsevier, 2021)
Summary: Multisystemic inflammatory syndrome (MIS-C) can develop as a complication of SARS CoV-2 infection, involving the gastrointestinal system mainly by vasoconstriction, edema, glandular hyperplasia, and a procoagulant state leading to direct tissue injury. Method: ology: a series of cases including 8 patients with MIS-C treated in two highly complex institutions is presented. These patients, had abdominal symptoms of surgical management. Results: The average age was 9.5 years and the most frequent symptoms were fever, abdominal pain, diarrhea (100%); in addition, 87.5% presented shock. The diagnosis of SARS CoV-2 was confirmed by RT-PCR test in 37.5%, antigen 12.5% and the rest of the patients showed IgM and IgG antibodies. In laboratories, the increase in acute phase reactants, Erythrocyte Sedimentation Rate (ESR), C-reactive protein, procalcitonin, as well as troponin, D dimer and proBNP, is highlighted. The surgical outcome documented 2 patients with a normal appendix, 3 patients with edematous appendicitis, and 3 patients with complicated appendicitis. Conclusions: patients with MIS-C display abdominal symptoms similar to those present in surgical emergencies and a non-negligible number of cases require surgical exploration. This condition poses a new differential diagnosis to the surgical abdomen in pediatric patients.